A cartilha Ler a Jato e o método audiofonográfico de alfabetização da professora Gilda de Freitas Tomatis - Dietrich, Mara Denise Neitzke (2012)
This study presents the analysis from the production of Ler a Jato primer and the Literacy audio-phonographic method in 15 hours, written by the teacher Gilda de Freitas Tomatis, at 1960 decade, in Rio Grande do Sul. The period of this study considered the 1967 year, when it was edited the first primer sample of Ler a Jato until 1986, was the last date found during this research. For the data analysis it was done a crossing of the documents with the oral sources. Related to the oral sources, it was considered the semi structured interview with the teacher Gilda de Freitas Tomatis‟ daughter in Porto Alegre city, in October of 2010. Related to the documents were considered: photos, books, primers, vinyl discos, certificates, medals, a view from Researches Center and Educational Advising from Education and Culture Bureau of 1968, all them including a detailed evaluation about the Ler a Jato primer. Some of these documents were donated by the teacher Gilda Tomatis‟ daughter, along with other documents acquired at tallow and websites. About the theoretical-methodological option, this study was based on the epistemological model of evidentiary paradigm proposed by Ginzburg (2007), used as a research device to notice and to analyze the relevant elements in the documents. This way, these study results intend to contribute with the other searches in the Literacy History and Textbooks areas, showing important aspect regarding the production and the textbooks circulation which were done by the teacher Gilda de Freitas Tomatis through her Tomatis-Textbooks Publisher, based on the communications circuit proposed by Darnton (1995). Furthermore, this study still presents a comparative analysis between the Ler a Jato primer and the Primeiro Guia de Leitura LER from MEC, material used in Brazil since the late 1940s. The analysis from these primers displayed similarities between both of them, specially related to graphic aspects, for example, distribution and similarities between some images, page organization, lessons and the use of some key-words, among other things.